PROBLEM ASPECTS OF IMPLEMENTATION OF THE EDUCATIONAL FUNCTION BY DISTANT FAMILIES (Psychology Travelogs, 2024)
The article analyzes the problematic aspects of the implementation of the educational function by distant families. The psychological features of the distant family were studied. communication at a distance, on the basis of a violation of mutual understanding and mutual interest, took on a formal and routine character.  It was revealed that the loss of a direct communication link led to formal and role-based forms of communication, which was directly reflected in the psychological state between members of a distant family; episodic communication thanks to Internet technologies does not allow to fully assess and follow the dynamics of the child's development, especially in adolescence, to support him precisely at the moment when he urgently needs parental advice.Psychological signs of a distant family are the absence or significant dysfunction of at least one element in the system of family relationships (goals, order of functioning, inconsistency of goals, energy of the system, lack of activity, lack of focus on family development), as well as the low quality of family functioning to the point of complete inability to fulfill family duties, which ultimately leads to unsatisfaction of the basic needs of family members.It was found that the most acute problems in the process of personality formation of a teenager from distant families are a long separation from one of the parents, a lack of physical and emotional communication with parents, frequent conflicts arise due to the lack of active communication, as well as problems of adaptation of family members to meetings and new divorces, difficulties in organizing communication at a distance. This provokes emotional cooling to the need for parental love and care, causes feelings of anxiety, maladjustment and social insecurity.
Keywords: distant family; educational function; functional family roles; psychological and emotional distance